2022
DOI: 10.3390/cells11243959
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Regulatory Role of ncRNA in NAFLD: A Particular Focus on PPARs

Abstract: Liver diseases are responsible for global mortality and morbidity and are a significant cause of death worldwide. Consequently, the advancement of new liver disease targets is of great interest. Non-coding RNA (ncRNA), such as microRNA (miRNA) and long ncRNA (lncRNA), has been proven to play a significant role in the pathogenesis of virtually all acute and chronic liver disorders. Recent studies demonstrated the medical applications of miRNA in various phases of hepatic pathology. PPARs play a major role in re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 229 publications
0
5
0
1
Order By: Relevance
“…PPARγ expression. Clinical trials have indicated that increased insulin resistance and hepatic PPARγ expressions were associated with NASH scores in some obese patients(Lee, Muratalla et al, 2023a, Mukherjee, Wanjari et al, 2022. Activation of PPARγ in the liver induces the adipogenic program to store fatty acids in lipid droplets as observed in adipocytes (Lee et al, 2018).…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…PPARγ expression. Clinical trials have indicated that increased insulin resistance and hepatic PPARγ expressions were associated with NASH scores in some obese patients(Lee, Muratalla et al, 2023a, Mukherjee, Wanjari et al, 2022. Activation of PPARγ in the liver induces the adipogenic program to store fatty acids in lipid droplets as observed in adipocytes (Lee et al, 2018).…”
mentioning
confidence: 99%
“…In this study, Snhg3 overexpression induced an increase in hepatic PPARγ and CD36.Although the administration of PPARγ antagonist T0070907 aggravated hepatic steatosis owing to an inhibition of adipogenesis in adipose tissue, it improved Snhg3-induced hepatic steatosis. Even though PPARγ's primary function is in adipose tissue, patients with MASLD have much higher hepatic expression levels of PPARγ, reflecting the fact that PPARγ plays different roles in different tissues and cell types(Mukherjee et al, 2022). Thus, understanding how the hepatic PPARγ expression is regulated will help develop prevention and treatments for MASLD(Lee et al, 2018).Epigenetics plays a crucial role in many physiological and pathological situations(Peixoto, Cartron et al, 2020).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Mukherjee et al summarize the role of PPARs and non-coding RNAs in non-alcoholic fatty liver disease (NAFLD) [ 44 ]. They introduce the causes and pathology of NAFLD and describe the roles of the different PPAR isoforms in this disease.…”
mentioning
confidence: 99%